L’agir respectueux de l’environnement comme but de la politique - Norbert Campagna (VertigO)
In this contribution the State is conceived as an instrument permitting the creation of the conditions of possibility of moral acting in general, and hence of environmental moral acting in particular. The initial hypothesis is that individuals can encounter obstacles to their acting morally. The major obstacles (epistemic, economic, material, cultural, moral) will be identified and we will then see which of these obstacles a democratic and liberal State, committed to the rule of law, may eliminate without violating its constitutive principles.